(untitled) (Modern information system and technologies, 2018)
The article considers the influence of information security factors on the functioning of a web resource with two-tier architecture. The model of availability of a web resource, its states and possible transitions between them is considered. The influence of the parameter of intensity of preventive measures on the availability index and the behavior of its change over time is investigated. Recommendations on the establishment of certain limits of change in the intensity of prevention are suggested.